Orthrus: a Pumilio-family gene involved in fruiting body and dark stipe development in Coprinopsis cinerea - Benedek Szathmári; Balázs Bálint; Botond Hegedüs; Máté Virágh; Zhihao Hou; Zhihao Hou; Xiao-Bin Liu; Hongli Wu; Csenge Földi; Julien Gagneur; Julien Gagneur; Johann Promeuschel; et al. (Frontiers in Fungal Biology)
Fruiting bodies of mushroom-forming fungi (Agaricomycetes) are complex multicellular structures whose formation is regulated by a developmental program that dynamically responds to environmental changes, such as light intensity. However, the genetic architecture and regulation of this developmental program are poorly known. Here, we characterize a novel Pumilio family gene, ort2, which influences fruiting body development, particularly the formation of dark stipes, a light-dependent alternative developmental trajectory. Phylogenetic analysis of this RNA-binding protein family in fungi revealed a distinct subfamily structure, with high conservation of each subfamily within Agaricomycetes. Reverse genetics experiments in the model species Coprinopsis cinerea revealed that ort2 disruptants produced fruiting bodies, but were deficient in dark stipe formation, whereas the overexpression mutants produced significantly more dark stipes. The gene was named after Orthrus, the two-headed dog of classical mythology, based on rare but reproducible branching fruiting body phenotypes observed upon overexpression. Our findings reveal fruiting-related functions for ort2, a novel conserved RNA-binding protein, and may serve as a novel entry point for understanding the molecular basis of dark stipe development.